Attitudes on AI adoption in accounting offices - Jokinen, Roni (My University, 2024)
Artificial intelligence is a growing phenomenon in the Finnish accounting industry. Yet, research around its adoption in accounting offices is scarce. The purpose of this thesis is to investigate what affects AI adoption in Finnish accounting offices. It will provide guidance to both accounting offices and service providers to examine the importance of the factors that affect AI adoption. It also aims to investigate the degree of development needed in different areas that contribute to more receptive behaviour, to determine how ready accounting offices are to adopt AI and to find different segments among potential users. In the field of technology adoption, multiple frameworks have been created to better understand the factors behind adoption decisions. From these, unified theory of acceptance and use of technology is utilized in this thesis. There is a plethora of research applying this theory in technology and AI adoption literature, but it is unused in accounting literature, which has concentrated on finding factors through qualitative means. In this thesis, a quantitative approach is deployed. The UTAUT framework is expanded with the results from expert interviews, and quantitatively assessed with data from a survey sent to accounting office employees. The research confirmed the UTAUT constructs to be significant in the Finnish accounting industry, and introduces a new construct of job risk, which was found to be significant factor as well. The level of automation in an accounting office is also theorized to be a significant factor by itself. Multiple moderations were found from which experience with AI influenced performance expectancy and effort expectancy remarkably. The results have many implications including the need for training and a focus on performance-related topics in marketing efforts.
Keywords: Artificial intelligence adoption, UTAUT, accounting